High‐efficiency sample preparation approach to determine acrylamide levels in high‐fat foods. Issue 15 (8th July 2016) - Li, Xiaodan; Li, Jinwei; Cao, Peirang; Liu, Yuanfa
Abstract : An improved sample preparation method was developed to enhance acrylamide recovery in high‐fat foods. Prior to concentration, distilled deionized water was added to protect acrylamide from degradation, resulting in a higher acrylamide recovery rate from fried potato chips. A Chrome‐Matrix C18 column (2.6 μm, 2.1 × 100 mm) was used for the first time to analyze acrylamide levels using ultra high performance liquid chromatography coupled with electrospray ionization tandem mass spectrometry, displaying good separation of acrylamide from interference. A solid‐phase extraction procedure was avoided, and an average recovery of >89.00% was achieved from different food matrices for three different acrylamide spiking levels. Good reproducibility was observed, with an intraday relative standard deviation of 0.04–2.38%, and an interday relative standard deviation of 2.34–3.26%. Thus, combining the improved sample preparation method for acrylamide analysis with the separation on a Chrome‐Matrix C18 column (2.6 μm, 2.1 × 100 mm) using ultra high performance liquid chromatography coupled with electrospray ionization tandem mass spectrometry is highly useful for analyzing acrylamide levels in complex food matrices.